Characterization, identification, and analysis of bioactive compound of endophytic bacteria from Hoya multiflora Blume - Dewinta Nur Alvionita; SRI RAHAYU; NISA RACHMANIA MUBARIK (Society for Indonesian Biodiversity, 2020)
Hoya multiflora Blume has been used for various purposes. Extract hoya has been reported to have bioactivity but extraction from the plant has been inefficient because it requires large biomass. Therefore, one of the appropriate ways to extract its bioactive compounds is using endophytic bacteria. The purposes of this research were to isolate, characterize, test its antimicrobial activity against two pathogenic bacteria  and identify its bioactive compound. A total of 18 isolates from H. multiflora Blume were successfully obtained. Based on antimicrobial test, one isolate was able to inhibit Escherichia coli, one isolate inhibited Staphylococcus aureus and two isolates inhibited both of pathogenic bacteria. In addition, minimum inhibitory concentration (MIC) of ethyl acetate extract from HMB 1 was 62.5 ppm, while from HMD 4 was 125 ppm, both against E. coli and S. aureus. Based on 16S rRNA gene sequencing analysis, HMB 1 was the most similar (99.91%) with Bacillus siamensis KCTC-13613 and HMD 4 was the most similar (100%) with Bacillus aryabhattai B82W22. Using GC-MS, pyrollo[1,2-a]-pyrazine-1,4-dione was found to be dominant compound in the exctract  bacteria of HMB 1and HMD 4 while Stigmasterol was found in extract HMD 4 and extract leaves H. multiflora Blume, respectively.